The Strategy of Turn-Taking in Pygmalion by George Bernard Shaw - Najlaa Hayyawi Abbar (Academia Open, 2023)
This scientific article examines the turn-taking system and adjacency pairs in George Bernard Shaw's play "Pygmalion" to gain insights into the rules and characteristics of conversational interaction. The study aims to investigate the adoption of turn-taking rules and components in the selected texts, analyze the structure of the texts, and explore the tactics employed in written texts related to turn-taking rules, elements, preference systems, and adjacency pairs. Through a meticulous analysis of the selected texts, it is revealed that the data adheres to the criteria of the turn-taking system and includes both adjacency pairs and insertion sequences. The findings contribute to the understanding of the turn-taking theory and its application in analyzing discourse. The implications of this research highlight the importance of understanding the systematic nature of turn-taking in facilitating successful exchanges in conversations and provide valuable insights for conversation analysts, linguists, and professionals in the field of discourse analysis. Highlights: Analysis of turn-taking system and adjacency pairs in "Pygmalion" play. Investigation of turn-taking rules, components, and tactics employed in written texts. Findings demonstrate adherence to turn-taking criteria and presence of adjacency pairs and insertion sequences. Keywords: Turn-Taking System, Adjacency Pairs, Conversation Analysis, Discourse Analysis, Pygmalion